PERAYAAN MAULID NABI SAW DI ACEH (ANALISIS SOSIOLOGI: AKULTURASI BUDAYA ACEH DENGAN BUDAYA ARAB) - Alfurqan (LPPM IAI Almuslim Aceh, 2023)
The people of Aceh celebrate the birthday of the Prophet Muhammad SAW every year. This fact raises the question, whether the Prophet's birthday. as a Shari'a or a form of culture? These two questions prompted the author to research the Prophet Muhammad's birthday tradition, which was pursued through library research. This research was conducted by exploring Islamic views on the existence of the Prophet Muhammad's birthday (normative). The history and cultural optics of Islam in Aceh and in Arabia, especially those related to the traditions of the Prophet Muhammad's birthday, are also the objects of research in this research. This research uses secondary data made from primary law in the form of the Koran and Hadith and secondary data made from secondary law in the form of works by legal experts. The works of cultural experts and enlycopedias provide complementary data. The results of the research concluded that the celebration of the birthday of the Prophet Muhammad saw was one of the Islamic cultures created by Muslims in the 4th/10th century AD which aimed to strengthen the love of Muslims for the Prophet Muhammad. and also as a medium for concern and friendship with fellow Muslims as a manifestation of the Muslim community's gratitude to Allah SWT. Birthday of the Prophet SAW. is the result of ijtihad, so its position as the second source of religious teachings as reported by Harun Nasution is teachings that originate from the explanations and thoughts of religious leaders or experts where the criteria are not absolute, and can be changed according to current developments. Meanwhile, the first teaching is a revelation from God, is absolute, absolutely true, eternal, unchanging and cannot be changed (shari'a).